2014
DOI: 10.1037/a0036394
|View full text |Cite
|
Sign up to set email alerts
|

Honey, I got fired! A longitudinal dyadic analysis of the effect of unemployment on life satisfaction in couples.

Abstract: Previous research on unemployment and life satisfaction has focused on the effects of unemployment on individuals but neglected the effects on their partners. In the present study, we used dyadic multilevel models to analyze longitudinal data from 2,973 couples selected from a German representative panel study to examine the effects of unemployment on life satisfaction in couples over several years. We found that unemployment decreases life satisfaction in both members of the couple, but the effect is more pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 79 publications
(164 reference statements)
3
59
1
4
Order By: Relevance
“…We also point out that our paper substantively differs from Luhmann et al (2014), who study 2973 couples in the GSOEP during the years 1984-2009 and document their life satisfaction trajectories before and after unemployment using research methods from the psychology discipline. The models that the authors use have a number of limitations.…”
mentioning
confidence: 88%
“…We also point out that our paper substantively differs from Luhmann et al (2014), who study 2973 couples in the GSOEP during the years 1984-2009 and document their life satisfaction trajectories before and after unemployment using research methods from the psychology discipline. The models that the authors use have a number of limitations.…”
mentioning
confidence: 88%
“…When they are unemployed, their wives' unemployment appears to alleviate the well-being loss from unemployment. Luhmann et al (2014), using German SOEP data, find that both men and women suffer from their partner's unemployment only if they are employed, but not if they are unemployed themselves.…”
Section: Introductionmentioning
confidence: 98%
“…Which factors are responsible for the interactions between the two partners' employment statuses found by Clark (2003), Luhmann et al (2014)? One could imagine that unemployment becomes easier to bear if the partner is unemployed as well because this might make it easier to structure the day and to have contacts with other people.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that partners were similar with regard to both level and slope of the happiness trajectory. Also, in a longitudinal study with a nationally representative sample of couples from Germany, the life satisfaction of partners was correlated both before and after becoming unemployed (Luhmann, Weiss, Hosoya, & Eid, 2014). It is important to note that, although these studies were longitudinal, they do not inform about the potential causes of codevelopment in romantic relationships.…”
Section: Life Satisfactionmentioning
confidence: 99%